Structures of Experience and Dispositions of Being: Review of Philippe Descola, Beyond Nature and Culture - Granjou, Céline (Humanimalia, 2014)
Philippe Descola. Beyond Nature and Culture. [Par-delà Nature et Culture. Paris : Gallimard, 2005.] Translated by Janet Lloyd. Chicago: University of Chicago Press, 2013. 488p.